Measuring the extent to which listed companies comply with sustainability accounting standards by improving performance and financial reporting to enhance confidence in financial statements: بحث تطبيقي مقارن في عينة من الشركات العراقية والعربية (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The objective of this research is to know the extent to which Iraqi and Arab companies apply the criteria of accounting for sustainability and disclosure, as well as to analyze the content of the annual financial reports of the companies listed in the financial market to determine their compliance with the Sustainability Accounting Standards Board )SASB(. Annual Report The commitment of telecommunications companies to implement sustainability issues related to the standard of telecommunications services reached a general average of (54%) for the sample of the research sample. This means that there is a degree of admissibility in applying the standard. As well as the highest level of reporting to the criterion of the (Jordan Telecom) sample of the year 2017, where the ratio was about (74%) and indicates the good proportion in the application of the standard. In addition, the opinions of a group of individuals in the companies (the sample of the research) were identified through the distribution of the questionnaire. The purpose of the questionnaire is to enhance the results of the research. It also shows that the topics of sustainability in the sectors of communication, transport and industry Financial statements to enhance confidence in the financial statements